DEGRADATION KINETICS OF ACETATE AND PROPIONATE BY IMMOBILIZED ANAEROBIC MIXED CULTURES - KUS, F; WIESMANN, U (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
The paper presents a short review of kinetics describing the anaerobic degradation of acetate and propionate by mixed cultures of bacteria. The authors discuss their measurements in lab scale extended fixed bed reactors containing porous polyurethane particles of different sizes for the immobilization of anaerobic mixed cultures. It can be demonstrated that the influences of diffusion within the particles can be neglected for the reactors under study. The results for both acetate and propionate degradation can be fitted by Haldane kinetics using the unionized fatty acid as the actual substrate. Product inhibition of propionate degradation by acetate is shown and described as a non-competitive product inhibition.
Keywords: ANAEROBIC DEGRADATION; ACETATE; PROPIONATE; KINETICS; LIMITATION; INHIBITION; DIGESTION; METHANOGENESIS; FERMENTATION; METHANE; BACTERIUM; HYDROGEN; ACIDS; Engineering; Environmental Sciences & Ecology; Water Resources